Դերանվան թվի քերականական կարգի ուսուցումը բուհում - Մինասյան, Ս. Ա.
В данной статье тема раскрывается в типологическом аспекте. In the given article the theme is considered by the typological aspect.
Keywords: Հայոց լեզվի մեթոդիկա